PENINGKATAN LITERASI AKADEMIK MAHASISWA PPIC MELALUI WORKSHOP PENULISAN ARTIKEL ILMIAH TERINDEKS SINTA - Fatonah, Feti; Sadiatmi, Rini; Kurniawan, Wahyu; K, Lilis; Eriyandi, Eriyandi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The ability to write scientific articles is an essential form of academic literacy for students in meeting the demands of the academic world and scientific publication. However, many students still struggle to produce scientific papers that comply with proper academic writing conventions and the publication standards of SINTA-indexed journals. This community service activity aims to improve the academic literacy of PPIC students through a one-day workshop on scientific article writing. The implementation method was participatory, involving the delivery of materials and hands-on practice in writing scientific articles. The results of the activity indicate an improvement in students’ understanding of scientific writing structure, citation techniques, and manuscript conformity with SINTA journal formats. Based on the pre-test and post-test results, this activity proved to be effective as an initial step in strengthening students’ academic literacy toward national scientific publication